Reveals Learning Problem Posing Mathematics In Primary School - Sarah Tombokan; Mieke O Mandagi (Annpublisher, 2025)
Background. Math class, especially in primary school, has always been a “big monster” for many students. Teachers are also having difficulties in delivering in the classroom. However, there are some options available for addressing these problems. Aims. This chapter offers problem-based learning and project-based learning as its solutions. Both solutions are explained briefly yet clearly, including their “how-to” and their barriers. Methods: Problem-based learning and project-based learning are employed as teaching methods that engage students in real-world problems, creating a personally meaningful experience.Conclusion. some barriers in implementing both of the solution options. They are: (1) role changing of teachers from knowledge resource into facilitator, (2) lack of experience for teachers, (3) good resource availability, (4) support from stakeholders, (5) technology support, and (6) careful teaching plan. However, all of them can still be solved based on each solution.While the barriers can be overcome in the learning process, there are also some critical considerations that teachers should be aware of when solving math class problems.